Mangroves in the North Rupat Landscape: Community Perceptions of Existence and Management - Gusniati Gusniati; Yusmar Yusuf; Mita Rosaliza (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
Mangrove ecosystems play a critical role in coastal protection and the livelihoods of coastal communities, yet their sustainability is strongly influenced by how local people perceive mangrove existence and management. This study examines public perceptions of mangrove existence and management in Tanjung Medang and Teluk Rhu Villages, North Rupat District, and identifies factors shaping these perceptions. A quantitative descriptive approach was applied using a structured Likert-scale questionnaire. From a population of 1,514 households, 48 respondents were selected using Slovin’s formula with a 10% margin of error and simple random sampling. Data were analyzed using descriptive statistics and a one-sample t-test with a benchmark value of 108 (75% of the maximum ideal score). The results show that public perception of mangrove existence is positive across all components (total score 2,493), with the highest score in mangrove condition/state (1,212). Perceptions of mangrove management are fairly good (total score 3,671), although supervision/monitoring is rated negative (938), indicating a key weakness in oversight. Most respondents demonstrate high perception (85.4%) and high knowledge (87.5%) regarding mangrove existence and management. Factor analysis indicates that knowledge is the dominant factor influencing perception (score 2,069), while social, economic, and cultural factors are not dominant. The one-sample t-test confirms that the overall perception score is significantly above the benchmark (t = 9.342; p < .001; mean difference = 20.708). These findings suggest that strengthening mangrove governance in North Rupat should prioritize improving supervision and monitoring mechanisms, while sustaining community education and outreach to reinforce knowledge-based support for conservation.